UX-RIVIS: Visualização da Informação sobre dados de UX baseado em revisões de aplicativos - Campos, Ariel Emanuel Sebastian (2023)
User Experience (UX) encompasses all aspects of the interaction between the user and a system. Thus, one way to obtain improvements in UX is through the Information Visual- ization area (InfoVis), which offers techniques for building visualizations that highlight the most important information to help users obtain relevant information from their data. In mobile software development, user reviews in app stores have proven to be a promising source for software developers to obtain information about the usability and UX of applications, in addition to being a direct channel of communication for users over time. of development. Thus, the present study had the general objective of assisting the development of mobile software by analyzing user reviews through UX data visualiza- tions. To this end, the methodology was organized into five stages (Stage A — Literature investigation; Stage B — Systematic Literature Mapping (MSL); Stage C — Recommen- dations for creating visualizations; Stage D — Construction of visualizations; and Stage E — Evaluation of the Proposal). Stage A reached a theoretical basis for carrying out this dissertation. Step B aimed to identify the state of the art in the literature on data visualization. Thus, 21 articles were read in full, demonstrating the methods, tools, and approaches used to build visualizations. Step C involved creating recommendations for building visualizations, using the results found in Step B, resulting in 16 recommendations. In Stage D, four visualizations called UX-RIVIS were developed to assist in analyzing application user reviews. Finally, Stage E consisted of an evaluation of UX-RIVIS with 23 software professionals. To this end, four tasks were applied in which professionals had to interact with each of the visualizations created. The results indicated that the participants understood the objective proposed by the visualizations, but they had difficulties carrying out the tasks proposed for the two of them. In general, a visualization proposal was made available to assist software developers in analyzing user reviews of applications.